Geolocalização de acidentes de trânsito da cidade de Mossoró – RN - Saraiva, Mayra Crisitna Monteiro (Universidade Federal Rural do Semi-Árido, 2018)
Geolocation is a tool that can be used in several ways, one of which is to assist data analysis, which was used in the work, seeking a better understanding of where accidents occur in the city of Mossoró - RN. With the analysis made, it was possible to map the points of the accidents and to see in which situation and how it happened. This information of knowing where the accident happened, facilitates in the decisions to diminish the occurrence. Having a more qualified road safety on the streets is a point to be treated in the city, as it was seen that as the years passed the number of accidents increased.
Keywords: Geolocalização; Segurança viária; Vias urbanas; Geolocation; Road safety; Urban roads; ENGENHARIAS::ENGENHARIA CIVIL